Career Opportunities in Agriculture and Allied Sciences - Rana, N.; Agnihotri, M. K.; Chetti, M. B.; Rathore, N. S. (Indian Farming, 2018)
The opportunities are available towork as research scientist, teacher,Marketing Manager, science writer,Quality Control Officer orproduction in-charge in the food,chemical and pharmaceuticalindustry, Analyst (Venture-Capitalist)Environmental /Safety Specialist.Biotechnology companies requirecorporate executives with business/management degrees. A graduate inbiotechnology can get a job ingovernment sector such asuniversities and colleges, researchinstitutes or at private centers asresearch scientist/assistant.